Recent advances in extruded polylactic acid-based composites for food packaging: A review - Han Lyn, F.; Ismail-Fitry, M. R.; M. A., Noranizan; Tan, Tai Boon; Z. A., Nur Hanani (Elsevier, 2024)
This review article provides a comprehensive overview of recent progress in polylactic acid (PLA) extrusion, emphasizing its applications in food packaging. PLA has witnessed a significant rise in demand, particularly within the food packaging sector. A notable increase in research publications has been observed in recent years, exploring the extrusion of PLA and PLA-based composite films. In comparison to conventional techniques such as solvent casting, extrusion offers advantages in scalability and environmental sustainability, especially for industrial-scale production. The benefits of this method include faster drying times, enhanced flexibility, consistent film thickness, and less structural defects. Extensive research has focused on the effect of various PLA blends on film properties, including flexibility, elongation, and barrier properties against water vapour and gases. Furthermore, the incorporation of compounds such as antioxidants, antimicrobials, and natural pigments has enabled the development of active and intelligent PLA-based packaging. This article summarizes the types of additives employed to enhance the physicochemical properties of extruded PLA and film performance. Additionally, this article explores the diverse applications of extruded PLA in active and intelligent packaging for various food products.